Sediment and associated phosphorus dynamics in meandering floodplain wetlands in the Tsitsa River catchment - Schlegel, Philippa Kirsten (Rhodes University, Faculty of Science, Department of Geography)
A key function of floodplain wetlands systems is their ability to remove and store sediments and associated particulates (such as nutrients, organic carbon, and contaminants) from water, thus improving water quality for downstream ecosystems and water users. Increases in sediment and nutrient inputs to drainage networks pose a serious challenge to integrated resource management. These issues can be partly mitigated through natural buffering solutions along drainage networks, such as preserving essential wetland systems like floodplains. However, their trapping efficiency and storage timescales are uncertain. Although a large body of international knowledge and literature has advanced our understanding of river-floodplain systems and the ecosystem services that they provide, the factors determining their likelihood and effectiveness in supplying those regulatory ecosystem services have not been extensively and scientifically tested in floodplain systems in South Africa. This research aimed to describe and quantify the regulatory ecosystem services related to sediment and phosphorus buffering dynamics of two meandering floodplain systems in the Eastern Cape, South Africa. The study examined the geomorphology, sedimentology, and historical rates of sediment and associated phosphorus accumulation and release in the two floodplain systems. These systems varied in their morphometric features, size, catchment location, and predominant land use, providing a diverse range of characteristics. A comparative analysis was conducted between the two systems to understand the influence of local and catchment-scale factors. Time-averaged suspended sediment samples from the two wetlands were used to compare suspended sediment and associated total phosphorous fluxes over annual scales. Although both floodplains were net depositional during the study period, contemporary suspended sediment mass balance calculations suggested that the relatively larger Minnehaha floodplain system (~1.5 kmÂ²) situated in a significantly smaller catchment (~40 kmÂ²) had notably higher sediment and associated phosphorus trapping efficiencies of 44 % and 49 % respectively, compared to 16 % and 8 % for the relatively small Gatberg floodplain system (~0.3 km2) situated in a much larger catchment (~135 kmÂ²). This variability is attributed to the interaction between annual rainfall regimes, sediment supply, sediment composition, relative wetland size to catchment area and wetland geomorphic character. To test the hypothesis that the suspended sediments and associated total phosphorus were retained by the adjacent floodplain system and to determine which parts of the two floodplains were most effective for retaining suspended sediments and phosphorus, concurrent measurements of sediment accretion were made at 6 sites in different geomorphic features in each of the floodplains. This was achieved using Cesium-137 and Lead-210 (Hereinafter referred to as Â¹Â³â ·Cs and Â²Â¹â °Pb) dating techniques. In-field observations suggested that all geomorphic units are still active and are frequently inundated during overbank flood flows. The average overbank sediment deposition and total phosphorus accumulation rates were 9376.9 g-sediment mÂ¯Â² yrÂ¯Â¹, 0.8 g-TP mÂ¯Â² yrÂ¯Â¹ for the Gatberg floodplain and 11802.8 g-sediment mÂ¯Â² yrÂ¯Â¹, 1.0 g-TP mÂ¯Â² yrÂ¯Â¹ for the Minnehaha floodplain. Deposition rates were temporally and spatially highly variable and dependent on the sediment supply, microtopographic relief, sinuosity, distance from the channel, the mode of inundation, and the extent of retention pondage. Overall, high average deposition rates were associated closest to the channel within the proximal floodplain zone (9712.1 g-sediment mÂ¯Â² yrÂ¯Â¹, 1.0 g-TP mÂ¯Â² yrÂ¯Â¹ for the Gatberg floodplain; 13541.1 g-sediment mÂ¯Â² yrÂ¯Â¹, 1.0 g-TP mÂ¯Â² yrÂ¯Â¹ for the Minnehaha floodplain) where the highest Dâ‚…â‚€ particle sizes (25.4 Î¼m for the Gatberg and 32.8 Î¼m for the Minnehaha) and percentage sand fractions (15 % and 21 %, respectively) were found. This may reflect the coarse nature of the sediment and the frequent connectivity to the channel, suggesting rapid accumulation is linked to a larger particle size which was deposited more readily in this zone. In the Gatberg system, the backswamp zone had one of the highest sedimentation rates and second highest phosphorus accumulation rates (13806.8 g-sediment mÂ¯Â² yrÂ¯Â¹, 0.9 g-TP mÂ¯Â² yrÂ¯Â¹). This was attributed to the additional coarse sediment inputs from the uncapped gravel forestry road that runs adjacent to the floodplain margin. In contrast, the backswamp zone within the Minnehaha River floodplain system had the lowest sedimentation rates (2005.9 g-sediment mÂ¯Â² yrÂ¯Â¹, 0.1 g-TP mÂ¯Â² yrÂ¯Â¹, which is what would be expected for the zone furthest away from the channel. In both floodplains, oxbows were important fine-sediment and phosphorus retention features (7126.0 g-sediment mÂ¯Â² yrÂ¯Â¹, 0.6 g-TP mÂ¯Â² yrÂ¯Â¹ for the Gatberg floodplain; 10101.0 g-sediment mÂ¯Â² yrÂ¯Â¹, 1.1 g-TP mÂ¯Â² yrÂ¯Â¹). Phosphorus distribution patterns were mainly attributed to variations in organic matter content and iron concentrations in fine-grained sediment deposits, while particle size distributions were less important. Using a mass balance approach the trapping efficiencies of the two floodplain systems were estimated. The average trapping efficiency for the Gatberg River floodplain accounts for 16 % of the suspended sediment yield (1317.5 tonnes-sediment yrÂ¯Â¹) and 8 % of the suspended sediment-associated total phosphorus yield (0.093 tonnes-TP yrÂ¯Â¹). Deposition on the Minnehaha floodplain accounts for an average of 44 % (1073.6 tonnes-sediment yrÂ¯Â¹) and 49 % of the suspended sediment-associated total phosphorus yield (0.098 tonnes-TP yrÂ¯Â¹). Within the Gatberg and Minnehaha River floodplain systems, the sediment sinks (oxbow and backswamp geomorphic zones) accounted for 13 % and 6 % (1070.6 tonnes-sediment yrÂ¯Â¹ and 0.069 tonnes-TP yrÂ¯Â¹); and 28 % and 33 % (683.2 tonnes-sediment yrÂ¯Â¹ and 0.066 tonnes-TP yrÂ¯Â¹), respectively, of the mean proportion of the total sediment and associated phosphorus yield. The zone of potential exchange (the proximal floodplain geomorphic zone) within the Gatberg floodplain system was calculated to trap 3 % (247.1 tonnes-yrÂ¯Â¹) of the mean proportion of the total sediment yield and 2 % (0.023-tonnes yrÂ¯Â¹) of the mean proportion of the total associated-phosphorus yield. Within the Minnehaha floodplain, this zone was estimated to trap 16 % (390.4 tonnes-sediment yrÂ¯Â¹ and 0.032 tonnes-TP yrÂ¯Â¹) of the mean proportion of both the total sediment and associated total phosphorus yield. These results indicate the importance of the distal floodplain reaches and oxbows as sediment and phosphorus storage hotspots. While floodplains mainly result from the accumulation of sediment, they're often modified and altered by erosion processes. Channel erosion and avulsions (e.g. meander bend cutoff events) are natural dynamic processes and form two of the principal processes of meandering river migration. During two wet seasons, both Gatberg and Minnehaha River floodplain areas experienced a mix of deposition and erosion, with slightly higher erosion observed in the Gatberg River reach. Channel bed scouring was prevalent in most cross-sections, suggesting limited sediment accumulation within the main channel beds. Volumetric estimates of sediment loss from meander migration were calculated by analysing cross-sectional data from 2019 and 2021 surveys to determine median and maximum eroded volumes, which were then converted to mass and scaled to tonnes per year for each river's eroded meander bends. The eroded sediment volumes were estimated as 520 tonnes yrÂ¯Â¹ for the Gatberg and 360 tonnes yrÂ¯Â¹ for the Minnehaha. The time sequence analysis using historical aerial images (between 1958, 1966, 1993, and 2015) revealed a few channel planform changes due to meander bend cutoff events in both river reaches. These events influence river morphology, increasing local channel slope, reducing sinuosity, and limiting floodplain access while impacting sediment and phosphorus flux. In the Gatberg system, changes in land use, such as increased road density from commercial forestry activities, likely drove channel straightening to accommodate higher sediment and bed loads. In the Minnehaha system, agricultural practices and livestock tracks likely increased sediment loads and hillslope-channel connectivity, driving channel changes. The results from the geochronology of two nested oxbows on the Gatberg floodplain estimated lateral migration rates of ~0.03 m yrÂ¯Â¹. The floodplain reworking rates of the Gatberg River floodplain are low compared to other systems in humid regions around the world, although, the Gatberg system compares well with migration rates of rivers in dryland regions. This study highlights the potential for floodplains undergoing regular flooding to be effective natural buffers along the sediment and phosphorus cascade in dryland landscapes. It enhances our comprehension of how sediment accumulates over time on floodplains within South African river systems, shedding light on both spatial and temporal patterns. These insights can contribute to better methodologies for evaluating the services provided by floodplain wetlands. These results can inform management decisions by offering a deeper understanding and allowing for the quantification of the cost-benefit of floodplain restoration and preservation actions in South Africa.,Thesis (PhD) -- Faculty of Science, Faculty of Science, Geography, 2024
Keywords: Sediments (Geology); Phosphorus; Sedimentation and deposition; Ecosystem services Law and legislation -- South Africa; Arid regions -- South Africa